Prognostic Factors for Health Outcomes After Exercise Therapy and Education in Individuals With Knee and Hip Osteoarthritis With or Without Comorbidities: A Study of 37, 576 Patients Treated in Primary Care. Issue 11 (31st July 2022) - Pihl, Kenneth; Roos, Ewa M.; Taylor, Rod S.; Grønne, Dorte T.; Skou, Søren T.
Abstract : Objective: To identify prognostic factors for health outcomes following an 8‐week supervised exercise therapy and education program for individuals with knee and hip osteoarthritis (OA) alone or with concomitant hypertension, heart or respiratory disease, diabetes mellitus, or depression. Methods: We included individuals with knee and/or hip OA from the Good Life With OsteoArthritis in Denmark (GLA:D) program. GLA:D consists of 2 patient education sessions and 12 supervised exercise therapy sessions. Before GLA:D, participants self‐reported any comorbidities and were categorized into 8 comorbidity groups. Twenty‐one potential prognostic factors (demographic information, clinical data, and performance‐based physical function) gathered from participants and clinicians before the program were included. Outcomes were physical function using the 40‐meter Fast‐Paced Walk Test (FPWT), health‐related quality of life using the 5‐level EuroQol 5‐domain (EQ‐5D‐5L) index score, and pain intensity using a visual analog scale (VAS; range 0–100) assessed before and immediately after the GLA:D program. Within each comorbidity group, associations of prognostic factors with outcomes were estimated using multivariable linear regression. Results: Data from 35, 496 (40‐meter FPWT) and 37, 576 (EQ‐5D‐5L and VAS) participants were included in the analyses. Clinically relevant associations were demonstrated between age, self‐efficacy, self‐rated health, and pain intensity and change in 40‐meter FPWT, EQ‐5D‐5L, or VAS scores across comorbidity groups. Furthermore, anxiety, education, physical function, and smoking were associated with outcomes among subgroups having depression or diabetes mellitus in addition to OA. Conclusion: Age, self‐efficacy, self‐rated health, and pain intensity may be prognostic of change in health outcomes following an 8‐week exercise therapy and patient education program for individuals with OA, irrespective of comorbidities.